Implementasi Pembelajaran Discovery Reasearch untuk Meningkatkan Prestasi Belajar Ekonomi Akuntansi Materi Laporan Rugi dan Laba Pada Siswa Kelas XII IPS 2 SMA Negeri 2 Siak Hulu - Rosliana Harahap (Journal on Education, 2020)
This research was based on problems related to economic learning achievement in class XII IPS 2 SMA Negeri 2 Siak Hulu. The solution to this problem was applying discovery research learning. The purpose of this research was to improve the learning achievement of economics through discovery research learning in class XII IPS 2 SMA Negeri 2 Siak Hulu. Based on the results of the analysis, it was found that student learning achievement had increased from cycle I to cycle III, namely, cycle I (67.6%,), cycle II (81%), cycle III (91%). The conclusion of this research is that the Discovery Research Method can improve student achievement in SMAN 2 Siak Hulu Class XII IPS 2 for the 2019/2020 academic year, and this learning model can be used as an alternative for implementing learning material in Economics. The teaching model of the Discovery Research Method can make students feel they get attention and the opportunity to express opinions, ideas, ideas and questions. Students can work independently or in groups, and are able to be responsible for all individual and group tasks. The application of learning with the Discovery Research Method has a positive effect, which can increase student learning creativity.